Neoadjuvant immunotherapy for non-small cell lung cancer: right drugs, right patient, right time? - Nick Pavlakis; Ken O'Byrne; Elizabeth Ahern; Brett G M Hughes; Ben J Solomon; Rina Hui (Journal for ImmunoTherapy of Cancer)
Standard curative treatment of early-stage non-small cell lung cancer (NSCLC) involves surgery in combination with postoperative (adjuvant) platinum-based chemotherapy where indicated. Preoperative (neoadjuvant) therapies offer certain theoretical benefits compared with adjuvant approaches, including the ability to assess on-treatment response, reduce the tumor bulk prior to surgery, and enhance tolerability in the preoperative setting. Indeed, the use of neoadjuvant therapies are well established in other cancers such as breast and rectal cancers to debulk the tumor and guide ongoing therapy, and neoadjuvant chemotherapy has similar efficacy but less toxicity in NSCLC. More recently, immune checkpoint inhibitors (ICI) targeting programmed death-1 (PD1)/PD1-ligand 1 (PD-L1) have transformed the treatment of advanced NSCLC; the unique mechanisms of action of ICI offer additional rationale for assessment in the neoadjuvant setting. Preclinical studies in mouse cancer models support the proof of concept of neoadjuvant ICI (NAICI) through improvement of T-cell effector function and long-term memory induction. Preliminary early-phase human trial data support the proposition that NAICI in NSCLC may provide an feasible and potentially efficacious future treatment strategy and large, randomized phase III trials are currently recruiting to assess this approach. However, outstanding issues include defining optimal treatment combinations which balance high efficacy with acceptable toxicity, validating biomarkers to aid in patient selection, and avoiding potential pitfalls such as missing a window for successful surgery, that is, choosing the right drugs, for the right patient, at the right time. Predictive biomarkers to direct selection of therapy are required, and the validation of major pathological response (MPR) as a surrogate for survival will be important in the uptake of the neoadjuvant approach.